2016
DOI: 10.1007/s11356-016-6839-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological impact of arsenic on earthworms and collembolans as affected by attributes of a highly weathered tropical soil

Abstract: High levels of heavy metals in soils may impose serious impacts on terrestrial organisms. In Brazil, the prevention values for evaluating the ecological risk of these elements are based only on soil chemical analyses and/or on data from ecotoxicological assays performed in soils of temperate regions. However, the attributes of the Brazilian highly-weathered tropical soils can influence the availability of heavy metals for soil fauna, resulting in different toxic values. To provide more accurate ecotoxicologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 39 publications
2
1
0
Order By: Relevance
“…In general, it was found that total As concentration in soil was not the crucial factor that determined the response of earthworms. Similar results were also reported by other researchers (Alves et al, 2018 ; Romero-Freire et al, 2015 ) who conducted the experiments on spiked soils and emphasized the importance of factors that determined arsenic solubility in soils, such as pH, soil texture and organic matter content. The effects of pH seem to be crucial mainly because soil pH strongly affects the solubility of As, while its direct impact on earthworms in not that important because E. fetida itself tolerates a broad range of soil pH from 4.0 to above 7.0 (Edwards & Arancon, 2022 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In general, it was found that total As concentration in soil was not the crucial factor that determined the response of earthworms. Similar results were also reported by other researchers (Alves et al, 2018 ; Romero-Freire et al, 2015 ) who conducted the experiments on spiked soils and emphasized the importance of factors that determined arsenic solubility in soils, such as pH, soil texture and organic matter content. The effects of pH seem to be crucial mainly because soil pH strongly affects the solubility of As, while its direct impact on earthworms in not that important because E. fetida itself tolerates a broad range of soil pH from 4.0 to above 7.0 (Edwards & Arancon, 2022 ).…”
Section: Resultssupporting
confidence: 90%
“…The latter effect should be probably explained by the fact that the weight was only determined for those individuals that survived, which may have had a particular individual resistance to arsenic. A similar interpretation was provided by Alves et al ( 2018 ) who also reported a significant trend to increasing earthworm weights at the highest As concentrations in soils. They explained it by a higher tolerance of the biggest earthworms to arsenic exposure, or by the fact that those individuals that survived benefitted from reduced density in soil and higher food availability that enabled them to grow bigger.…”
Section: Resultssupporting
confidence: 85%
“…All tubs were covered with gunny bags and the moisture content was maintained constant between 40-45% by sprinkling water. In order to prevent the likelihood of pre-exposure to contaminants, healthy adult earthworms (400-500 mg) from third generation were used as test organisms (Alves et al, 2018). The heavy metals used in this experiment were sodium arsenate (AR/ACS) (Na 2 HAsO 4 7H 2 O) and potassium dichromate (GR) (K 2 Cr 2 O 7 ) purchased from Hi-Media.…”
Section: Earthworms and Chemicalsmentioning
confidence: 99%